CORRIGENDUM: Predicting diabetic self-care management based on the theory of planned behavior among elderly with type 2 diabetes in Thailand (Diabetes Mellitus.2019;22(3). DOI: 10.14341/dm10290) - Paleeratana Wongrith (Сахарный диабет)
A corrigendum on « Predicting diabetic self-care management based on the theory of planned behavior among elderly with type 2 diabetes in Thailand» by Paleeratana Wongrith (2019). Diabetes Mellitus. 22(4). doi: 10.14341/DM10290There are some errors on the page 368: source [11] should be replaced by [9], [12] – [11], [13] – [12], [14] – [13], [15] – [14].The author apologizes for this error and state that this does not change the scientific conclusions of the article in any way.The original article has been updated.